Giuseppe Garibaldi and Sweden: Between Solidarity and Scandinavism - Monica Quirico (Nordicum-Mediterraneum, 2008)
The book entitled Scandinavia: Her Fears and Her Hopes, written in French, was published on February 29, 1856, in Paris, where representatives of the European Powers were discussing peace negotiations with Russia ensuing the end of the Crimean War. The author, Gustaf Lallerstedt, a moderate liberal, a diplomat, and majority shareholder of the liberal newspaper "Aftonbladet", was first in outlining a parallelism between the proactive role played by Piedmont in Italy's unification and the similar one that Sweden, in his opinion, ought to take upon herself vis-à-vis Scandinavian unity. Lallerstedt's aim was also to warn the European nations against the Russian threat; in this perspective, strengthening the United Kingdom of Sweden and Norway (established in 1814) could provide an effective remedy.